Avaliação do uso do arcview 3.2a na análise de mercado - Cristiano das Chagas Dantas e Roberto Rosa; Roberto Rosa (Revista Sociedade & Natureza, 2004)
Companies from various segments have invested humam and financial resources in seeking a constat improvement in their logistical network. Knowing its own consumer market and analyzing it by the geographical aspects may mean the differential amongst the competitors. The Geographical Information Systems are adequate and modern tools for modeling e dealing whit problems related to spatial data distribution, involving either the customers´location through its addresses, or through products destination. In this papework it was evaluated the usage of Arcview 3.2 Software in spatial broadcast of aa database informations from a retailer company, besides the possibility of generating solutions involving networks review.